The dermatophyte Trichophyton rubrum secretes an EDTA-sensitive alkaline phosphatase on high-phosphate medium - Ferreira-Nozawa, Monica S. [UNESP]; Nozawa, Sérgio R.; Martinez-Rossi, Nilce M.; Rossi, Antonio (FapUNIFESP (SciELO), 2003)
In this communication, we show that the growth of isolate H6 of the dermatophyte Trichophyton rubrum on non-buffered medium and under saturating phosphate conditions is dependent on the initial growth pH, with an apparent optimum at pH 4.0. In addition, irrespective of the initial growth pH, the pH of the medium altered during cultivation reaching values that ranged from 8.3 to 8.9. Furthermore, this isolate synthesized and secreted almost the same levels of an alkaline phosphatase with an apparent optimum pH ranging from 9.0 to 10.0 when grown on both low- and high-phosphate medium. Also, this alkaline phosphatase is activated by Mg2+ and is EDTA-sensitive. On the other hand, the very low levels of the enzyme retained by the mycelium grown on buffered medium at pH 5.0-5.2 suggest that this enzyme is encoded by an alkaline gene, i.e., a gene responsive to ambient pH signaling.
Keywords: Alkaline phosphatase; Ambient pH; Dermatophytes; Enzyme secretion; Pi sensing; Trichophyton rubrum; Arthrodermataceae